Penerapan Media Pembelajaran Berbasis Google Sites di SMA Negeri 1 Tembilahan Hulu - Eriska Wahyuni; Nefilinda Nefilinda; Ade Irma Suryani (LaGeografia, 2022)
AbstractThis study aims to determine the application of learning media based on Google Sites and teacher responses as well as student responses to the application of learning media based on Google Sites on the learning outcomes of students in class X IPS SMA N 1 Tembilahan Hulu. This type of research is a quasi-experimental. The research subjects were students of class X IPS 1, X IPS 2, X IPS 3 and Class X IPS 4 who were taking geography lessons hydrosphere theme at SMA N 1 Tembilahan Hulu in the academic year 2021/2022. totaling 135 students. The results of the study are: 1) The application of Google Sites-based learning media in geography subjects has a significant effect on the learning outcomes of class X students of SMAN 1 Tembilahan Hulu. The results of the t-test obtained a significant value of 0.000 <0.05, meaning that Ha is accepted and H0 is rejected. 2) Teacher responses and student responses to the application of Google Sites-based learning media are 71.96% and student responses are 76.58%. AbstrakPenelitian ini bertujuan untuk mengetahui penerapan media pembelajaran berbasis Google Sites dan respon guru serta respon peserta didik terhadap penerapan media pembelajaran berbasis Google Sites terhadap hasil belajar siswa kelas X IPS SMA N 1 Tembilahan Hulu. Jenis penelitian adalah kuasi eksperimen. Subjek penelitian adalah siswa kelas X IPS 1, X IPS 2, X IPS 3 dan Kelas X IPS 4 yang mengikuti pembelajaran geografi dengan tema hidrosfer di SMA N 1 Tembilahan Hulu tahun pelajaran 2021/2022 berjumlah 135 siswa. Hasil penelitian adalah:  1) Penerapan media pembelajaran berbasis Google Sites pada mata pelajaran geografi berpengaruh signifikan terhadap hasil belajar siswa kelas X SMAN 1 Tembilahan Hulu. Hasil uji t diperoleh nilai signifikan 0,000 < 0,05, artinya Ha diterima dan H0 ditolak. 2) Respon guru dan respon siswa terhadap penerapan media pembelajaran berbasis Google Sites sebesar 71,96% dan respon siswa sebesar 76,58%.